2021
DOI: 10.3390/cancers13194954
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Stratification of Childhood Ependymomas as a Basis for Personalized Diagnostics and Treatment

Abstract: Ependymomas are among the most enigmatic tumors of the central nervous system, posing enormous challenges for pathologists and clinicians. Despite the efforts made, the treatment options are still limited to surgical resection and radiation therapy, while none of conventional chemotherapies is beneficial. While being histologically similar, ependymomas show considerable clinical and molecular diversity. Their histopathological evaluation alone is not sufficient for reliable diagnostics, prognosis, and choice o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 96 publications
(193 reference statements)
0
11
0
Order By: Relevance
“…The PF-A subgroup represents 90% of posterior fossa tumors and occurs mainly in young patients, with a median age of 3 years, a slight prevalence of males, and has a worse prognosis, with lower overall and disease-free survival (19)(20)(21)(22). In molecular studies, hypermethylation of CpG islands and global hypomethylation of DNA are observed and on immunohistochemical analysis with H3K27me3 (Figure 11), and a global reduction of this histone confirms the diagnosis.…”
Section: Histopathological Classificationmentioning
confidence: 84%
See 3 more Smart Citations
“…The PF-A subgroup represents 90% of posterior fossa tumors and occurs mainly in young patients, with a median age of 3 years, a slight prevalence of males, and has a worse prognosis, with lower overall and disease-free survival (19)(20)(21)(22). In molecular studies, hypermethylation of CpG islands and global hypomethylation of DNA are observed and on immunohistochemical analysis with H3K27me3 (Figure 11), and a global reduction of this histone confirms the diagnosis.…”
Section: Histopathological Classificationmentioning
confidence: 84%
“…These are differentiated by the degree of DNA methylation and CpG islands, which can be evaluated by immunohistochemical analysis with H3K27me3 (15)(16)(17). Notably, the PF-A and PF-B subgroups are still molecularly heterogeneous, pointing to a future distinction into additional subgroups according to the expression of specific gene families (18)(19)(20).…”
Section: Histopathological Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…( Figure 6 ). In particular, the gain of chromosome 11, 13, 17, 20, and 21 identified in this case are highly specific for MPE [ 12 , 13 , 14 ].…”
Section: Resultsmentioning
confidence: 99%